Extreme Programming for Developing Additional Employee Income System (Case Study: Karangasem Regency Government) - I Putu Noven Hartawan (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
The State Civil Apparatus (ASN) is an important part of the government. ASN performance measurement needs to be done, because besides ASN being the provider in terms of community service, performance measurement is also used as a reference in providing additional employee income. Karangasem regency government developed a system to measure the performance of the existing 6,449 ASNs. The system is applied to measure performance and as a system that provides additional employee income. However, the pandemic situation resulted in the Karangasem district government having to press the budget for developing this system. The researcher proposes the Extreme Programming (XP) approach in system development. XP, which has the value of Communication, Simplicity, Feedback and Courage, is the right choice in developing a system with a small budget and time. Feedback that is quickly handled also greatly influences the speed and cost of development